2021
DOI: 10.1186/s41182-021-00330-2
|View full text |Cite
|
Sign up to set email alerts
|

Community-based geographical distribution of Mycobacterium ulcerans VNTR-genotypes from the environment and humans in the Nyong valley, Cameroon

Abstract: Background Genotyping is a powerful tool for investigating outbreaks of infectious diseases and it can provide useful information such as identifying the source and route of transmission, and circulating strains involved in the outbreak. Genotyping techniques based on variable number of tandem repeats (VNTR) are instrumental in detecting heterogeneity in Mycobacterium ulcerans (MU) and also for discriminating MU from other mycobacteria species. Here, we describe and map the distribution of MU g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…The prevalence of mycobacteria identified in the biofilm was higher in Côte d'Ivoire compared with Ghana. Even though other studies found a higher prevalence of MU DNA in biofilms from aquatic plants (Williamson et al, 2008;Williamson et al, 2014;Narh et al, 2015), this study comparatively found a higher prevalence in the rivers as found in a similar study conducted in Cameroun (Zeukeng et al, 2021). There was also a higher proportion of the ER domain gene amplification in biofilm from aquatic plants compared with those found in open water in Ghana and Côte d'Ivoire.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The prevalence of mycobacteria identified in the biofilm was higher in Côte d'Ivoire compared with Ghana. Even though other studies found a higher prevalence of MU DNA in biofilms from aquatic plants (Williamson et al, 2008;Williamson et al, 2014;Narh et al, 2015), this study comparatively found a higher prevalence in the rivers as found in a similar study conducted in Cameroun (Zeukeng et al, 2021). There was also a higher proportion of the ER domain gene amplification in biofilm from aquatic plants compared with those found in open water in Ghana and Côte d'Ivoire.…”
Section: Discussioncontrasting
confidence: 75%
“…Oligonucleotide VNTR primers that amplify the VNTR region of MPM were synthesized by Sigma-Aldrich and Inqaba Biotech. PCR conditions for VNTR typing were adapted from research that targeted similar loci (Ablordey et al, 2005(Ablordey et al, , 2007Williamson et al, 2014;Narh et al, 2015;Zeukeng et al, 2021). A nested PCR for the environmental DNA was performed using the same conditions and primers, if no amplicon was initially obtained from the first PCR run.…”
Section: Genotyping and Confirmation Of Mycobacterium Ulcerans Dna In...mentioning
confidence: 99%
“…The "small flower field" is generally performed by two to three people. The small flower field is the core part of flower drum lantern dance [17]. If the "big flower field" is a passionate poem jointly created by many "Orchids" and "drums" and the collective "Ode to joy" and "Carnival dance" of farmers, then the dance performance with simple plot such as "grab handkerchief" and "grab bench" in the "small flower field" is the love story or lyric prose of one or two or three farmers [18].…”
Section: Flower Drum Lantern Is Closely Combined With Farmingmentioning
confidence: 99%
“…Genotyping techniques based on VNTR allow distinction between MU and other mycolactone-producing mycobacteria and provides strong evidence MU. VNTR profiling can be used to follow chains of transmission from the environment to humans [54] , [59] .…”
Section: Methodsmentioning
confidence: 99%